Excessive activation of JAK-STAT signaling contributes to inflammation induced by acute Vibrio infection in shrimp - Hongliang Zuo; Xiya Yang; Youxi Wang; Bangping Hu; Zhiming Zhu; Zhixun Guo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virulence)
Uncontrolled immune responses resulting from overactivated cellular signaling pathways, leading to inflammation and tissue injury, are a major cause of death in pathogen-infected individuals. This phenomenon has been well studied in mammals but is less explored in invertebrates. Bacteria of the genus Vibrio are among the most harmful pathogens to humans and aquatic animals. In shrimp, Vibrio infection is generally characterized by the sudden onset of disease, with pathological signs of opaque and whitish muscle tissue. The current study shows that shrimp acutely infected with high dose of Vibrio parahaemolyticus develop inflammation-like pathological changes, leading to rapid death. Excessive activation of JAK-STAT signaling, rather than the Dorsal and Relish pathways, results in overactivation of shrimp immunity and is a major cause of inflammation induced by acute Vibrio infection. Weakening JAK-STAT signaling attenuates the inflammatory response and reduces mortality caused by acute Vibrio infection in shrimp, whereas enhancing JAK-STAT signaling can convert a normal infection into an acute one, accelerating shrimp death. Therefore, this study indicates that, similar to that in mammals, the pathogenesis of infectious diseases in invertebrates is complicated by inflammatory responses triggered by dysregulated immune signaling.